Prevention of carcinoma cervix in Bangladesh perspective - Noor, L; Gafur, MA; Ahmed, M; Ara, I (Mediscope, 2016)
Carcinoma cervix is a preventable disease. Etiological factor is known that is human papilloma virus (HPV). Two types of vaccines are available. Cervix is easily accessible allowing screening tests possible. Screening is simple and available. The disease has long premalignant phase that can be detected by screening. Although Pap smear is the gold standard method of screening, visual inspection with acetic acid (VIA) particularly single-visit approach, can be an appropriate alternative in Bangladesh considering our available health care facilities. If abnormal screening results (Pap test,VIA, HPV test), colposcopy and guided biopsy can be taken. Colposcopy can detect cervical intraepithelial neoplasia and early invasive carcinoma. Treatment in pre-invasive and early invasive carcinoma is found to be curative. Mediscope Vol. 3, No. 1: January 2016, Pages 33-39